(untitled) (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
Inventory management is the practice overseeing and controlling of the ordering, storage and use of components that a company uses in the production of the items it sells. Inventory management has been used as a decision-making in countless firms and has been extensively studied in the academic and corporate spheres. The purposes of inventory system are to know the details of the items including code, name, condition, location of items and the year of purchase. It is also to make easy for manage the item. Usually, creating inventory list can be done two ways either manually or computerized. Manually inventorying is usually written data with handwriting on the data books. It has many disadvantages. One of them is when the admin staff input the data, it is prone to be typographical errors. Here in the Computer Engineering Department in Rajamangala University of Technology Thanyaburi (RMUTT) the inventory management still using manual process for inventorying and collect the data of an item. This inventory management system will help the process inventorying using web-based application and also mobile application for collecting data information. Quick Response (QR) Code technology as a unique tagging solution for each item that store information from the server through the local network. The implementation of this system for Inventory Management System could be a solution for manage inventorying process and stored information of inventory through QR Code.